HUBUNGAN MINAT BELAJAR SISWA DENGAN HASIL BELAJAR SISWA DI KELAS II UPTD SD NEGERI 125138 PEMATANGSIANTAR - Fransius Jonathan Sitepu; Natalina Purba; Muktar B. Panjaitan (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to determine the relationship between students' interest in reading and student learning outcomes in class II UPTD SD Negeri 125138 Pematangsiantar. This research was carried out on Jl. Medan, simple. Kerang, Sumber Jaya sub-district, sub-district. Siantar Martoba. Pematang Siantar, to be precise at UPTD SD Negeri 125138 Pematangsiantar. In this research, researchers used a questionnaire method that was distributed to students which had previously been validated previously. The questionnaire used to collect data to analyze students' interest in reading in relation to students' learning outcomes in class II of SD Negeri 125138 Pematangsiantar l is by completing the check mark (√). Researchers took research samples from Class II of SD Negeri 12513 Pematangsiantar because they wanted to find out how much influence interest in reading has on learning outcomes. Researchers took samples in class II. In this research, it can be seen from the results of the correlation analysis between students' reading interest and student learning outcomes that it is 0.473, which is in the Medium category, because it is between the values of 0.400 - 0.600. The simple linear regression test shows that the calculated F value is 5,755 with a significant level of 0.02 < 0 .05 so it can be concluded that there is a significant influence between the variable interest in reading on learning outcomes, which is based on the student's reading interest on student learning outcomes in Class II SD Negeri 1251 38 Pematangsiantar is selbelsar 22 %.